Introducción al conocimiento de los hongos de Doñana (Huelva, España) - Calonge, Francisco de Diego; Tellería, María Teresa (Lazaroa, 1980)
Diego Calonge, E. de Telleria, MT. Catalogue of íhefungi of Doñana (Huelva, & Spain). Lazaroa, 2: 271-326 (¡980), As a result of the numerous botanical excursions carried out during 1977 and 1978 to the National Park of Doñana, in order to study the fungus flora of that interesting territory, it has been possihle to identify 168 species, which have been collected in the area compiled within the triangle Rota (Cádiz), Hinojos and Mazagón (Huelva). Most of the collected material was growing in coastal sand dunes, belonging to the Gaditano-OnuboAlgarviense chorological province (Rivas-Martínez & al. 1977). It has been found five new genera to the Spanish mycological catalogue: Bovistella Morg., Globulicium l-Ijortst., Botryohypochnus Donk, Clitocyhula (Sing.) Mét. & Streptothrix Corda, and 24 new species for the same catalogue: Cloniopsis levantica, Leucoscypha patavina. Hypoxilon serpens, Strep tothrix fusca. Sebacina calcea, Clitocybula lenta, Collybia konradiana. Crepidotus pu bes cens, Lepiota konradi¿ Melanoleuca decembris, Melanoleuca electropoda. Pluteus salar, Tn choloma aura¡um, Boíryobasidium candicans. Boíryohypochnus isabellinus. Fibuloporia my celiosa, Globulicium hiemale, Hyphoderma pallidum, Phellinus ri,nosus, Vararia rhodospora, Arachnion lloydianum, Bovina polymorpha, Bovista pusilli/'ormis. Bovistella radicata. <> Real Jardin Helénico. C.S.iC., Cuesta Claudio Moyano. 1 Madrid <7). 272 Lazaroa Vol? 2 (1980)